Student Character Building Methods on Distance Education - Rahmadini, Nurhaliza; Rasyid, Thariq Ahmad (International Journal of Ethno-Sciences and Education Research, 2021)
Character building is very important to be applied to the student at school. Students’ character affects their ethics and awareness of the right thing to do that leading them to be great decision-makers for themselves. This paper aims to discuss several methods to build students’ character in distance education. The methods used include: giving assignments, creating a comfortable learning environment, making a schedule, providing the chance to ask questions, making a learning consent, conducting some surveys, and watching movies. The results of the methods used indicate that the method is effective to be applied to the students during distance education with the support from parents, teachers, and students.